TECHNOLOGY OF JUICE AND POMEGRANATE COOKING AT HOME (Scientific journal of the Fergana State University, 2023)
The article provides information on the national economic importance of subtropical fruits, in particular pomegranate, on the development prospects of pomegranate orchards in the Fergana region, and also highlights the technology for obtaining juice and compote from pomegranate in home conditions.